Youth unemployment and society - Petersen, Anne C. 1944-; Mortimer, Jeylan T. 1943- (Cambridge University Press, 1994)
As societies become more technically advanced and jobs require more expertise, young people are forced into a prolonged state of social marginality. Employment during adolescence could provide significant experiences for growth into later work roles, but most societies are not equipped to provide adolescents with meaningful work experience. In Youth Unemployment and Society, historians, psychologists, economists and sociologists provide a cross-national examination of trends in youth unemployment and intervention strategies in the United States and Europe. Assessing the causes of aggregate societal unemployment rates, the authors address factors that make individuals more vulnerable to unemployment and consider the developmental consequences of this experience. The volume also examines how persistently high rates of youth unemployment affect society's values, beliefs and institutions
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Gesellschaft; Jugend; Psychologie; Youth / Employment / Congresses; Unemployment / Social aspects / Congresses; Unemployment / Psychological aspects / Congresses; Unemployed / Social conditions / Congresses; Unemployed / Psychology / Congresses; Social problems / Congresses; Jugendarbeitslosigkeit; Konferenzschrift